TRAINING IN THE PROCESSING OF WASTE PAPER INTO RECYCLED PAPER WITH SELLING VALUE - Hendri Mayanta; Romauli Pakpahan; Maswan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
The community service was carried out on July 20 2020, the location of the activity was the East Nagahuta Village Head Office, Jl. IN Panjaitan Kelurahan No. 45, Nagahuta Timur, Siantar Marimbun District, Pematang Siantar City, North Sumatra, 2114. This recycled paper can also be used to make various handicrafts that can be made by people who have creative values and an artistic spirit. Products made from recycled paper can be used as home decoration knick-knacks, stationery and office supplies, and unique and creative multi-purpose containers can be made that housewives are interested in. In addition, they can be used for craft assignments for students and school students. . Paper waste management certainly requires more attention,